New dataset of filiicolous lichens of five major species of Dipterocarpaceae in INIKEA Forest Rehabilitation Plot of Borneo - Mohammad Shahrul Shahpuan; Lauretta Andrew Laneng; Kok Chuong Looi; Yuta Inaguma; Charles Santhanaraju Vairappan (2019)
Rehabilitation of degraded forest is being intensified in Borneo, effort by the INIKEA Rehabilitation Project in Luasong (Sabah) has resulted in healthy growth of native timber species to Borneo. Slow growth rate of Dipterocarps has been attributed to presence of biofoulers on its leaves and herbivory. Therefore, an investigation was conducted to document the coverage and distribution of foliicolous lichens on the leaves of five common timber species Dipterocarpus conformis, Dryobalanops lanceolate, Dryobalanops keithii, Shorea ovalis, and Shorea fallax, planted during this project in 2008. Colonization of foliicolous lichen on timber species was seen to exist in two distinct pattern; leaves of genus Shorea showed surface colonization of 28–29%, while genus Dipterocarpus and Drybalanopsis exhibited a lesser coverage of 15–18%. A total of 32 species belonging to nine families were recorded during the course of this study. Lichen diversity was higher on leaves of Dipterocarpus conformis and Shorea ovalis as compared to the other three species. In addition, nine new records of foliicolous lichens were isolated, identified and their descriptions are presented here.